Optimizing Early Disease Detection among Adolescents through a School-Based Health Screening Program at SMA Al-Rifa’ie Malang - Lilis Masyfufah; Muhammad Yusuf Setiawan; Erwin Astha Triyono; Titin Wahyuni (STIKES Yayasan RS.Dr.Soetomo, 2026)
The development of health information technology has undergone a significant transformation. One important aspect that has changed is the method of screening or early detection of diseases, which is often carried out using applications that are easily accessible to the public. Given that cases of tuberculosis, hypertension, low vision, and mental health issues are on the rise due to lifestyle changes. This activity was carried out to introduce the health screening application owned by the government for widespread use in the community. The Methods Community service activities were carried out by giving presentations to the target audience (Al-Rifa'ie High School students) and asking them to practise screening using the introduced application. The Results showed 76% of participants were unaware of the existence of screening applications for these diseases. The provision of health information related to screening through presentations and practical demonstrations was effective in ensuring that participants understood the material because they participated actively.